2018
DOI: 10.1111/jpn.12974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of modified palygorskite supplementation on the growth performance, immunity, oxidative status and intestinal integrity and barrier function of broilers

Abstract: This experiment was designed to investigate effects of different levels of modified palygorskite (MPal) supplementation on growth performance, immunity, oxidative status and intestinal integrity and barrier function of broilers. A total of 320 1-day-old Arbor Acres broilers were randomly assigned into 5 dietary treatments and fed a basal diet supplemented with 0, 0.25, 0.5, 1 and 2 g/kg MPal, respectively, for a 42-day feeding trial. Treatments quadratically reduced feed/gain ratio (F:G) during 1-21 days and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In the current study, we observed that dietary MPal supplementation increased relative bursa of Fabricius weight and SIgA concentration in the jejunal and ileal mucosa at 42 days, and it was in agreement with the results by Yin et al [ 48 ] and Weaver et al [ 50 ]. Researches from our lab have illustrated that this MPal exerted better adsorption capacity to zearalenone [ 39 ], and improved immunity, intestinal antioxidant status, as well as barrier integrity of animals [ 37 , 38 ], which would, partially and eventually, result in better immune function of broiler chickens challenged with permitted feed concentrations of Fusarium mycotoxins in the present study.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In the current study, we observed that dietary MPal supplementation increased relative bursa of Fabricius weight and SIgA concentration in the jejunal and ileal mucosa at 42 days, and it was in agreement with the results by Yin et al [ 48 ] and Weaver et al [ 50 ]. Researches from our lab have illustrated that this MPal exerted better adsorption capacity to zearalenone [ 39 ], and improved immunity, intestinal antioxidant status, as well as barrier integrity of animals [ 37 , 38 ], which would, partially and eventually, result in better immune function of broiler chickens challenged with permitted feed concentrations of Fusarium mycotoxins in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…In broiler chickens, Chen et al have reported that dietary Pal supplementation could improve immunity via enhancing intestinal IgM and SIgA contents [ 34 ]. Similarly, improved immunity of broiler chickens was observed by appropriate levels of MPal addition in a recent investigation, as evidenced by increased IgM, IgG, and SIgA contents in the intestinal mucosa at 42 days [ 37 ]. Moreover, it has been proven that a modified clay (montmorillonite) could elevate serum IgG concentration in laying hens [ 49 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This finding was also consistent with that of Shen et al (). Immunoglobulins are an important component of the humoural immune system, which regulates the host's defensive immune response by different strategies, such as neutralizing viruses, phagocytosing antigen and antibacterial effects (Su et al, ). In this study, a significant increase in IgM and IgG levels was observed after LPS injection, and it was similar to the previous results of Kariyawasam Wilkie Hunter and Gyles (), who reported that LPS could induce the production of immunoglobulins and participate in the inflammatory response in broilers.…”
Section: Discussionmentioning
confidence: 99%